2018
DOI: 10.1111/ijfs.13729
|View full text |Cite
|
Sign up to set email alerts
|

Purification of polyphenols from kiwi fruit peel extracts using macroporous resins and high‐performance liquid chromatography analysis

Abstract: Summary An efficient strategy for the purification of polyphenols from kiwi fruit peel extracts was developed in this study. Six different macroporous resins were evaluated in static adsorption and desorption tests, and NKA‐II resin was used for further test because of its high adsorption capacity (21.28 mg g−1 dry resin) and desorption ratio (84.92%). The adsorption mechanism of the NKA‐II resin indicated that pseudo‐second‐order kinetics and the Freundlich isotherm model could adequately explain the adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
2
0
3
Order By: Relevance
“…The volatile aroma compounds of blueberries play an important role in enhancing taste. Nevertheless, the use of 1‐MCP may reduce the production of aromatic substances (Balbontín, Gaete‐Eastman, Vergara, Herrera, & Moya‐Leon, 2007; Guo, Qiao, Zhang, Ren, & Li, 2018), although it can delay the ripening of fruit. Furthermore, consumer difference tests indicated that people can differentiate the 1‐MCP‐treated apples from the control group (Marin, Colonna, Kudo, Kupferman, & Mattheis, 2009; Quan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The volatile aroma compounds of blueberries play an important role in enhancing taste. Nevertheless, the use of 1‐MCP may reduce the production of aromatic substances (Balbontín, Gaete‐Eastman, Vergara, Herrera, & Moya‐Leon, 2007; Guo, Qiao, Zhang, Ren, & Li, 2018), although it can delay the ripening of fruit. Furthermore, consumer difference tests indicated that people can differentiate the 1‐MCP‐treated apples from the control group (Marin, Colonna, Kudo, Kupferman, & Mattheis, 2009; Quan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Both PPE and CPE showed significantly lower (p < 0.05) reducing power with all concentrations tested compared to that of L-ascorbic acid; meanwhile, PPE exhibited a significantly higher (p < 0.05) reducing power than that of CPE with all concentrations tested. In summary, the reducing capacity of tested materials to Fe 3+ in this assay was as follows: L-ascorbic acid > PPE > CPE, and it demonstrated that PPE had stronger anti-oxidant activity than that of CPE, which could be due to its higher content of polyphenols (Guo et al, 2018).…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 78%
“…O kiwi é o fruto proveniente de uma planta de videira perene que sofre desfolhação, contém altos níveis de antioxidantes benéficos, como vitamina C, vitamina E, carotenóides e compostos fenólicos. De maneira mais abundante estão presentes os polifenóis, que são importantes componentes pois apresentam propriedades antioxidantes, antivirais, antigênicas, antimicrobianas e anticancerígenas e são utilizados em o tratamento de doenças cardiovasculares (GUO et al, 2018).…”
Section: Fundamentação Teóricaunclassified
“…These results are important because they demonstrate that the processing for flour preparation met the requirements for its future use in the manufacture of new food products. Com o crescimento do indústria de processamento de kiwi, houve também o aumento na geração de maior quantidade de resíduos, causando problemas econômicos e ambientais (GUO et al, 2018). Os resíduos de frutas (casca e semente) podem apresentar maior conteúdo nutricional do que as partes comestíveis.…”
Section: Introductionunclassified